4
$\begingroup$

How can $e^e$ be expressed in an infinite series with as much simplification as possible.

  • I wrote the series of $e^x$ by keeping $x$ as $e$ and from there I also expanded every $e$ in this expansion now I was thing about expanding it further by binomial theorem but I am not able to understand how can i use binomial theorem here and how much can this be simplified in another words I am trying to write this series as simple as expansion of $e$ , is it possible and how it can be done.

  • Any help will be highly appreciated , thanks in advance.

$\endgroup$
  • $\begingroup$ Have a look at the Wikipedia article Bell Number, particularly the intro and section 3.2 (Generating function). $\endgroup$ – DanielWainfleet May 28 '17 at 15:05
0
$\begingroup$

Let $f(x)=e^x$ Then $$f^{(1)}(x)=f^{(2)}(x)=...=f^{(n)}(x)=...=e^x, \forall x\in\Bbb R.$$ Then applying Taylor's theorem we get - $$f(x)=f(0)+xf^{(1)}(0)+\frac {x^2}{2!} f^{(2)}(0)+...+\frac {x^n}{n!} f^{(n)}(\phi), 0\lt\phi\lt1.$$ Then you will get $$e^x=1+x+\frac{x^2}{2!}+...$$ i.e. $$e^x=\sum_{n=0}^{\infty}\frac {x^n}{n!}$$ And hence $$e^e=\sum_{n=0}^{\infty}\frac {e^n}{n!}$$ $$=\sum_{n=0}^{\infty}\frac{\sum_{i=0}^{\infty}\frac{n^i}{i!}}{n!}.$$

$\endgroup$
  • $\begingroup$ Quoting the OP: "I wrote the series of $e^x$ by keeping $x$ as $e$". $\endgroup$ – Shaun May 28 '17 at 12:54
  • $\begingroup$ Actually first time that was my fault. I can understand that was e^e $\endgroup$ – gobinda chandra May 28 '17 at 13:38
  • $\begingroup$ Why are you down voting me ? $\endgroup$ – gobinda chandra May 28 '17 at 13:45
  • $\begingroup$ It is Lagrange's theorem or Taylor's theorem. $\endgroup$ – user449276 May 28 '17 at 15:51
3
$\begingroup$

$$e^e=\sum_{k\ge 0}\frac{e^k}{k!}=\sum_{k,\,l\ge 0}\frac{k^l}{k!l!}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.